Optimizing Raw Material Pre-Treatment for Bioethanol Production from Empty Fruit Bunches: A Comparative Study - Said Zul Amraini; Sunitha Sari; David Andrio; Waman Fatra; Reno Susanto (Graha Primera Saintifika, 2023)
Bioethanol (C2H5OH) is an organic chemical widely used as a solvent. It is also applied in producing germicides, beverages, antifreeze, fuel, and depressants as an intermediate in producing other chemical substances. Generally, bioethanol is generated from the fermentation of glucose (sugar) accompanied by a distillation process. This study aimed to optimize bioethanol production against variations in pre-treatment and solvent concentrations through enzyme hydrolysis and fermentation of oil palm empty fruit bunches. The pre-treatment is an important stage in the conversion process of lignocellulosic biomass, as it eliminates lignin, reduces the crystallinity of the cellulose, and increases the porosity of the substance, thereby facilitating the hydrolysis process and glucose fermentation. The process was carried out with different concentrations of acid, base, and organolsov solvents, after that, it was hydrolyzed using cellulase enzymes for 24 hours and fermented using Saccharomyces Cerevisiae yeast for 5 days. Furthermore, the bioethanol produced was separated through a rotary vacuum evaporator at 180 rpm and a temperature of 78 °C. The highest ethanol content produced was 7.8% with 4% NaOH and 90 minutes of pre-treatment residence time.